Legal Implications of Mixed Marriages on Joint Property Status - Mariana, Rasyid; Hadikusuma, Hidayati (Legal Frontier, 2025)
Mixed marriages, involving individuals of different nationalities, present complex legal challenges, particularly in determining the status of joint property. In the Indonesian legal system, such marriages are governed by a combination of national laws, including Law No. 1 of 1974 on Marriage, Law No. 12 of 2006 on Citizenship, and Law No. 5 of 1960 on Basic Agrarian Principles, among others. One of the most significant issues arises in relation to the ownership and control of immovable property, especially when one spouse is a foreign national. Indonesian law restricts foreign ownership of land, which affects the ability of couples in mixed marriages to hold joint property rights over land and housing. This often necessitates legal arrangements such as prenuptial agreements (perjanjian perkawinan) to separate assets, preventing legal conflicts and safeguarding property rights. The absence of such agreements can lead to the classification of joint property as incompatible with national land laws, potentially invalidating ownership claims. This paper explores the implications of mixed marriages on joint property status by analyzing Indonesian legal provisions, court rulings, and practical case examples. It also discusses the role of notaries and legal practitioners in drafting agreements that comply with the prevailing legal framework. The study emphasizes the importance of legal certainty, equal rights within marriage, and the harmonization of private international law principles with domestic statutes. Findings suggest the need for more accessible legal education and simplified mechanisms for asset regulation in mixed marriages to prevent unintended legal consequences